Black, Brown+ Latinx Design Educators : Conversations on Design and Race - Walters, Kelly (New York : Princeton Architectural Press, 2021)
Walker, David Jon ; Berry, Anne H. ; Romero, Samuel ; Abdullah, Nida ; Alejandro, Jason ; Rittner, Jennifer ; Suman, Shantanu ; Doughty, Ashley ; Tejada, Ramon ; Sales, Kaleena ; Qadeer, Ali Shamas ; Walters, Kelly
boek